Sampling Rate Effects on Resting State fMRI Metrics - Huotari, Niko; Raitamaa, Lauri; Helakari, Heta; Kananen, Janne; Raatikainen, Ville; Rasila, Aleksi; Tuovinen, Timo; Kantola, Jussi; Borchardt, Viola; Kiviniemi, Vesa J.; Korhonen, Vesa O. (Frontiers in Neuroscience, 2019)
Low image sampling rates used in resting state functional magnetic resonance imaging (rs-fMRI) may cause aliasing of the cardiorespiratory pulsations over the very low frequency (VLF) BOLD signal fluctuations which reflects to functional connectivity (FC). In this study, we examine the effect of sampling rate on currently used rs-fMRI FC metrics. Ultra-fast fMRI magnetic resonance encephalography (MREG) data, sampled with TR 0.1 s, was downsampled to different subsampled repetition times (sTR, range 0.3 - 3 s) for comparisons. Echo planar k-space sampling (TR 2.15 s) and interleaved slice collection schemes were also compared against the 3D single shot trajectory at 2.2 s sTR. The quantified connectivity metrics included stationary spatial, time, and frequency domains, as well as dynamic analyses. Time domain methods included analyses of seed-based functional connectivity, regional homogeneity (ReHo), coefficient of variation, and spatial domain group level probabilistic independent component analysis (ICA). In frequency domain analyses, we examined fractional and amplitude of low frequency fluctuations. Aliasing effects were spatially and spectrally analyzed by comparing VLF (0.01 - 0.1 Hz), respiratory (0.12 - 0.35 Hz) and cardiac power (0.9 - 1.3 Hz) FFT maps at different sTRs. Quasi-periodic pattern (QPP) of VLF events were analyzed for effects on dynamic FC methods. The results in conventional time and spatial domain analyses remained virtually unchanged by the different sampling rates. In frequency domain, the aliasing occurred mainly in higher sTR (1 - 2 s) where cardiac power aliases over respiratory power. The VLF power maps suffered minimally from increasing sTRs. Interleaved data reconstruction induced lower ReHo compared to 3D sampling (p < 0.001). Gradient recalled echo-planar imaging data produced both better and worse metrics depending on the metric. In QPP analyses, the repeatability of the VLF pulse detection becomes linearly reduced with increasing sTR. In conclusion, the conventional resting state metrics (e.g. FC, ICA) were not markedly affected by different TRs (0.1 - 3 s). However, cardiorespiratory signals showed strongest aliasing in central brain regions in sTR 1 - 2 s. Pulsatile QPP and other dynamic analyses benefit linearly from short TR scanning.